2017
DOI: 10.1002/cjce.22792
|View full text |Cite
|
Sign up to set email alerts
|

Comminution of biogenic materials

Abstract: Renewable resources have been gaining increasing importance for energy generation in recent years. Lignocellulosic biomass, as an alternative to limited crude oil, can be utilized to produce these chemicals. The upstream process of comminution is a key element in the use of renewable raw materials. However, comminution is a highly energy consumptive process, making it necessary to assess the benefits of fine comminution in terms of reducing energy consumption by an adequate characterization of the products. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 13 publications
0
25
0
4
Order By: Relevance
“…Based on the authors' own research, it was found that the angular speed of the discs and, consequently, the linear speed of the grinding blades, have a significant influence on the values of the integrated energy consumption of the preliminary process.Acquiring energy from biomass requires its earlier preparation: drying, grinding, palletizing, etc. [7]. These procedures require certain energy inputs (costs) which significantly decrease the energy and environmental balance in the entire lifecycle of the energy material (wood, grain biomass, etc.)…”
mentioning
confidence: 99%
“…Based on the authors' own research, it was found that the angular speed of the discs and, consequently, the linear speed of the grinding blades, have a significant influence on the values of the integrated energy consumption of the preliminary process.Acquiring energy from biomass requires its earlier preparation: drying, grinding, palletizing, etc. [7]. These procedures require certain energy inputs (costs) which significantly decrease the energy and environmental balance in the entire lifecycle of the energy material (wood, grain biomass, etc.)…”
mentioning
confidence: 99%
“…To better address how and if further parameters are relevant in the complex topic of comminution of renewable resources, further studies are required. minimal Martin diameter x 16 [mm] characteristic particle size value x 50…”
Section: Discussionmentioning
confidence: 99%
“…This is not necessarily related to the type of main stress. Other studies, conducted with the same raw material but other types of hammer mill construction, obtained contradictory results [16]. Therefore, it can be assumed that the design of the mill has a strong influence on the fineness of the comminution product.…”
Section: Particle Size Analysis Of the Comminution Productsmentioning
confidence: 97%
“…Der Wassergehalt von Holz hat bei der Zerkleinerung den signifikantesten Einfluss auf die für die Zerkleinerung benötigte Energie [19,20]. Der Wassergehalt von Holz hat bei der Zerkleinerung den signifikantesten Einfluss auf die für die Zerkleinerung benötigte Energie [19,20].…”
Section: Introductionunclassified
“…Des Weiteren liefert die Hammermühle bei allen Versuchen ein breiter verteiltes Produkt im Vergleich zur Schneidmühle. Diese starken Einflüsse des Mühlentyps zeigte sich auch bei Arbeiten mit anderen holzartigen Materialien[19,20].Im Rahmen der Arbeit wurden zusätzlich die Ergebnisse der zwei unterschiedlichen Arten der Charakterisierung, Siebanalyse und dynamische Bildanalyse mittels eines Camsizers, verglichen. Die Ergebnisse zeigen, dass entscheidend ist, welche Kenngrößen der dynamischen Bildanalyse mit dem Ergebnis der Siebanalyse verglichen werden.…”
unclassified